2016
DOI: 10.3390/catal6080120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu+/Cu2+ Ratio on the Catalytic Behavior of Anhydrous Nieuwland Catalyst during Dimerization of Acetylene

Abstract: Abstract:The relative contents of Cu + and Cu 2+ in solutions of anhydrous Nieuwland catalyst and CuCl 2 -added anhydrous Nieuwland catalyst were detected by X-ray photoelectron spectroscopy (XPS). Results indicated that Cu + could be transformed into Cu 2+ during the process of acetylene dimerization into monovinylacetylene, leading to deactivation of the catalyst. Moreover, the addition of Cu 2+ inhibited the oxidation of Cu + into Cu 2+ and enhanced the performance and lifetime of the catalyst. The optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Figure 2 B shows the Cu 2p spectrum for Cu-TCPP. The binding energy at 944.0 eV was assigned to the shake-up satellite peak of Cu 2+ ; a Cu 2p 3/2 (934.8 eV) peak and a Cu 2p 1/2 (954.7 eV) peak as well as two shakeup satellites in the Cu 2p spectrum confirmed the coexistence of two copper valence states, Cu 2+ and Cu + 27 . The relative atomic percentages of Cu 2+ and Cu + were determined by XPS to be 63% and 37%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Figure 2 B shows the Cu 2p spectrum for Cu-TCPP. The binding energy at 944.0 eV was assigned to the shake-up satellite peak of Cu 2+ ; a Cu 2p 3/2 (934.8 eV) peak and a Cu 2p 1/2 (954.7 eV) peak as well as two shakeup satellites in the Cu 2p spectrum confirmed the coexistence of two copper valence states, Cu 2+ and Cu + 27 . The relative atomic percentages of Cu 2+ and Cu + were determined by XPS to be 63% and 37%, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Han et al reported that the addition of DL-alanine to the Nieuwland catalyst can reduce the activity of acetylene dimerization and improve the MVA selectivity [25]. We also found that the addition of SrCl 2 [26], ZnCl 2 [27], PEGs [28], and CuCl 2 [9] can improve the selectivity of MVA or the lifetime of the catalyst. However, these modified catalysts can only improve either the acetylene conversion or MVA selectivity, and simultaneous improvements in conversion and selectivity have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 59%
“…However, our previous studies found that Cu 2+ also plays an important role in the acetylene dimerization reaction, and the deactivation of the anhydrous NC was caused by the transformation of Cu + to Cu 2+ [9]. Hence, valence changes for copper species in fresh and used NC and L1-NC were evaluated via high-resolution XPS, and the results are shown in Figure 9 and Table 4.…”
Section: Relationship Between the Valence Of Copper And Catalytic Actmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that Cu + is the main active component of the Nieuwland catalyst, and it has been reported in our previous work that the content of Cu + is related to the activity of the anhydrous Nieuwland catalyst [20]. Therefore, we investigated the valence charges of copper species using high-resolution XPS.…”
Section: Correlation Between the Amount Of Copper (I) And Catalytic Amentioning
confidence: 99%